Teen Births Keep American Crime High - Jennifer Hunt (Institute for the Study of Labor (IZA), 2003)
The United States has a teenage birth rate that is high relative to that of other developed countries, and falling more slowly. Children of teenagers may experience difficult childhoods and hence be more likely to commit crimes subsequently. I assess to what extent lagged teen birth rates can explain why the United States had the highest developed country crime rates in the 1980s, and why US rates subsequently fell so much. For this purpose, I use internationally comparable crime rates measured from the 1989-2000 International Crime Victims Surveys. I find that an increase in the share of young people born to a teen mother increases the assault rate. The type of assault affected is perpetrated by unarmed lone assailants known to the victim by name, particularly at home or at work, and is not reported to the police. The pattern of teen births in the United States explains ?30% of the relative fall in assaults by assailants known to the victim, but more than explains the 1980s gap with the rest of the world. I also present evidence on larceny and burglary.
Keywords: K42; J12; 330; crime; family structure; Kriminalität; Kinder; Mütter; Familiensoziologie; Schätzung; Vereinigte Staaten